Adversity Quotient (AQ): Effect of Physical Education On Adversity Quotient Levels - Zainur; Lardika, Rola Angga; Gazali, Novri; Daharis; Sulastio, Agus (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to determine the significance of the effect of physical education toward problem-solving skills to survive the problems (Adversity Quotient). This research was conducted to students SMAN 1 Teluk Kuantan Kabupaten Kuantan Singingi. The method applied was experiment with non-equivalent one group pretest posttest design. The procedures of this research were observation, interview, treatment program preparation, analysis and conclusion. The result showed a significant between inquiry learning in physical education with value (sig.), 000 <α = 0.005. Based on the data, we can conclude the inquiry learning gives a significant to the level of students’ adversity quotient (AQ).